MONEY PAYMENT SYSTEM DESIGN SCHOOL PUBLIC HIGH SCHOOL BUNDA KANDUNG, JAKARTA - Wahyu Utomo; Ir. Susi Wagiyati, MM (Jurnal Sistem Informasi, 1998)
If the proposed new system has been running, the obstacles encountered in a running system can be overcome immediately. The services provided to students can be moved quickly because of the aids, computer data also students who have paid the tuition can be stored with a good data  structure and at any time can be seen or repaired.